TYPOLOGY OF CHANGES IN AN ORGANIZATION AND THEIR CHARACTERISTICS - A. Pavlova (Russian Journal of Economics and Law)
The article is dedicated to defining the types of changes in a modern organization, the conditions necessary for changes implementation, and the technique of complex expert assessment of change necessity (CEACN).